Body Dysmorphic Disorder and Self-esteem in Adolescents and Young Adults with Acne Vulgaris - Benjamin G. Tros; Patrick M.J.H. Kemperman; Jade Kuckulus; Rick Hoekzema; Nienke C.C. Vulink (Acta Dermato-Venereologica, 2023)
Body dysmorphic disorder is a mental health disorder characterized by a preoccupation with a perceived flaw, which is commonly seen among dermatology patients. The objective of this study was to determine the frequency of body dysmorphic disorder and assess self-esteem among a clinical sample of adolescents and young adults being managed for acne vulgaris. A total of 105 patients, age range 13–24 years, receiving acne treatment at 1 of 2 dermatology outpatient clinic were included. A self-report questionnaire was used, which included a body dysmorphic disorder screening tool (based on the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) diagnostic criteria) and the Rosenberg Self-Esteem Scale (RSES). Acne was graded with the Cook’s acne grading scale. Out of 105 adolescents and young adults visiting a dermatologist due to acne, 13 (12.4%) screened positive for body dysmorphic disorder (95% confidence interval (95% CI) 6.8–20.2%). Patients with body dysmorphic disorder were more likely to have female gender (p = 0.020) and had lower self-esteem (RSES 15.8 vs 20.5, respectively, p = 0.013) compared with patients without body dysmorphic disorder. No differences were found in the frequency of body dysmorphic disorder with DSM-IV or DSM-5 criteria. This is the first study to report on the frequency of body dysmorphic disorder and self-esteem in adolescents and young adults with acne. Ultimately, more awareness of body dysmorphic disorder among adolescents and young adults presenting with dermatological disorders could lead to more rapid recognition and referral to psychiatric units.